The Iconographic Evolution of Patagonian and Fuegian Canids - Castro-Morales, S (BioMed Central Ltd, 2024)
Background: We assess the putative identity of canids accompanying the Patagonian and Fuegian aborigines through an iconographic timeline encompassing 1699–1894, when a number of narratives provided written descriptions and illustrations of those aborigines and their canids. We determine what type of “dogs” were those canids, disentangling their type or breed group, to reveal their characteristics, composition, and development during that period. Methods: We searched for illustrations published by navigators and explorers where the presence of canids was reported in the historical territory of the Patagonian aborigines (Aónikenk, Kawésqar, Manek enk, Sélk nam, and Yahgan). We constructed a matrix to record the descriptions of all canids represented in those illustrations. Their characterization included body size, coat, tail, ears, skull, and attitude, among others. We then classified whether they were morphologically closer to domestic dogs or to foxlike canids. We used the morphological appearance of dogs to classify them into breed types, whenever possible. Results and discussion: We identified and classified 61 canids from 26 illustrations in accounts published between 1699 and 1894. From a historical perspective, those accounts suggest that soon after the first contacts with Europeans, the Patagonian and Fuegian aborigines began to exchange and breed dogs of non-native origin, initiating an extended process of mixing between aboriginal foxlike canids and European dogs. From a cynological perspective, the foxlike canids associated with the aborigines were widely present only before 1833, exhibing an homogeneous appearance with a solid coat, pointed snout, small erect ears of high insertion, and fallen and bushy tail. After 1833, the canids depicted show a more varied appearance and mixed coat, with blunter snout, drooping ears at lower insertion, and erect fine tail with sparse hair. Most of these were hunting dogs morphologically similar to modern breeds such as pointers/setters, hounds, terriers, and retrievers. © The Author(s) 2024.